Yersinia effector protein (YopO)-mediated phosphorylation of host gelsolin causes calcium-independent activation leading to disruption of actin dynamics. - Singaravelu, P; Lee, W; Wee, S; Ghoshdastider, U; Ding, K; Gunaratne, J; Grimes, J; Swaminathan, K; Robinson, R (American Society for Biochemistry and Molecular Biology, 2017)
Pathogenic Yersinia bacteria cause a range of human diseases. To modulate and evade host immune systems, these yersiniae inject effector proteins into host macrophages. One such protein, the serine/threonine kinase YopO (YpkA in Yersinia pestis), uses monomeric actin as bait to recruit and phosphorylate host actin polymerization-regulating proteins, including the actin-severing protein gelsolin, to disrupt actin filaments and thus impair phagocytosis. However, the YopO phosphorylation sites on gelsolin and the consequences of YopO-mediated phosphorylation on actin remodeling have yet to be established. Here we determined the effects of YopO-mediated phosphorylation on gelsolin and identified its phosphorylation sites by mass spectrometry. YopO phosphorylated gelsolin in the linker region between gelsolin homology domains G3 and G4, which, in the absence of calcium, are compacted but adopt an open conformation in the presence of calcium, enabling actin binding and severing. Using phosphomimetic and phosphodeletion gelsolin mutants, we found that YopO-mediated phosphorylation partially mimics calcium-dependent activation of gelsolin, potentially contributing to a reduction in filamentous actin and altered actin dynamics in phagocytic cells. In summary, this work represents the first report of the functional outcome of serine/threonine phosphorylation in gelsolin regulation and provides critical insight into how YopO disrupts normal gelsolin function to alter host actin dynamics and thus cripple phagocytosis.